Marshallian vs Jacobs effects: which one is stronger? Evidence for Russia unemployment dynamics - Olga Demidova; Alena Kolyagina; Francesco Pastore (Global Labor Organization (GLO), 2019)
This paper is devoted to the study of diversification and specialization influence on one of the main indicators of Russian labour market, the unemployment growth. The purpose of the work is to find out which effects dominate in the Russian regions, Marshallian or Jacobs, and whether this predominance is stable for different time intervals. The following hypotheses were empirically tested: 1) the dependence of the unemployment rate on the degree of concentration or diversification is non-monotonic due to possible overlapping effects of urbanization and localization; 2) the influence of the degree of concentration or diversification on the level of unemployment depends on the time period. To test these hypotheses nonparametric additive models with spatial effects were used. Both hypotheses found empirical confirmation. It was shown that in Russia, depending on the period, various effects dominated: in 2008-2010, and 2013-2016 Marshallian effects predominated, while in 2010-2013, Jacobs effects dominated.
Keywords: C14; C21; J64; 330; concentration; diversification; unemployment; spatial effects; nonparametric models